Global satellite survey reveals uncertainty in landfill methane emissions - Matthieu Dogniaux; Joannes D. Maasakkers; Marianne Girard; Dylan Jervis; Jason McKeever; Berend J. Schuit; Shubham Sharma; Ana Lopez-Noreña; Daniel J. Varon; Ilse Aben (Nature, 2025)
Abstract Methane is a potent but short-lived greenhouse gas and rapid reductions of its anthropogenic emissions could help decrease near-term warming 1 . Solid waste emits methane through the decay of organic material, which amounts to about 10% of total anthropogenic methane emissions 2 . Satellite instruments 3 enable monitoring of strong methane hotspots 4 , including many strongly emitting urban areas that include solid waste disposal sites as most prominent sources 5 . Here we present a survey of methane emissions from 151 individual waste disposal sites across six continents using high-resolution satellite observations that can detect localized methane emissions above 100 kg h –1 . Within this dataset, we find that our satellite-based estimates generally show no correlation with reported or modelled emission estimates at facility scale. This reveals major uncertainties in the current understanding of methane emissions from waste disposal sites, warranting further investigations to reconcile bottom-up and top-down approaches. We also observe that managed landfills show lower emission per area than dumping sites, and that detected emission sources often align with the open non-covered parts of the facility where waste is added. Our results highlight the potential of high-resolution satellite observations to detect and monitor methane emissions from the waste sector globally, providing actionable insights to help improve emission estimates and focus mitigation efforts.